Evaluation of cytotoxic potential of loratadine and the combination of loratadine and cisplatin on hepatocellular carcinoma cell lines - Adly, Nouran (AUC Knowledge Fountain, 2018)
Hepatocellular carcinoma (HCC) has been a major health problem in Egypt with extensive efforts and studies done in enhancing chemotherapeutic drugs for more optimal results. Existing chemotherapeutic drugs are costly with problematic side effects. Recent studies have demonstrated the anticancer potential of antihistamines on different types of cancer, including HCC. Antihistamines have been proven to induce cell cycle arrest and/or apoptosis through different mechanisms depending on their role on different cancer types. The second generation antihistamine, loratadine (LOR), was found to have tumor inhibiting effects on human colon carcinoma cell line. However, no studies were done neither on the influence of loratadine on HCC cells, nor the effect of the combination of loratadine with existing chemotherapeutic drugs to test its potential to improve chemotherapy. Here, the cytotoxic potential of loratadine and the combination of loratadine and cisplatin on HepG2 and SNU449 were investigated. Cell viability assay was performed to show that there is a dose-dependent cytotoxic effect of LOR on both HCC cell lines and that there is a synergistic to additive effects when LOR was introduced to the cells in combination with cisplatin when the IC50 of both drugs were used. Loratadine did not show a cytotoxic effect on normal cells when used in low concentrations (<55.6 ÂµM). However, when used in higher concentration (<73.2 ÂµM), LOR showed a high cytotoxic effect. Apoptotic and cell cycle analysis showed that loratadine induced apoptosis and cell cycle arrest in the G2/M phase in SNU449 cells, while combination of loratadine and cisplatin may induce necrosis and cell cycle arrest in G2/M phase. Taken together, loratadine offers a strong basis to be further developed either alone or in combination with cisplatin as a treatment option for advanced hepatocellular carcinoma. Further studies are required to test the effect of loratadine treatment in vivo and perhaps to test the effect of loratadine in combination with sorafenib in vitro and in vivo for the hope to improve HCC therapy.